Surgical amputation for patients with diabetic foot ulcers: A Chinese expert panel consensus treatment guide - Liao, Xuan; Li, Sheng-Hong; El Akkawi, Mariya Mohamad; Fu, Xiao-bing; Liu, Hong-wei; Huang, Yue-sheng (Frontiers in Surgery, 2022)
Background: Diabetic foot disease is a serious complication of diabetes mellitus (DM). Patients with DM have a 25% lifetime risk of developing a foot ulcer, and between 14% and 24% of patients require a major or minor lower limb amputation due to severe gangrene, however, decisions concerning whether to amputate, whether to perform a major or minor lower limb amputation, and how best to determine the amputation plane remain unclear. Methods: To consolidate the current literature with expert opinion to make recommendations that will guide surgical amputation for patients with diabetic foot ulcers. A total of 23 experts experienced in surgical treatment for patients with diabetic foot ulcers formed an expert consensus panel, they presented the relevant evidence, discussed clinical experiences, and derived consensus statements on surgical amputation for patients with diabetic foot ulcers. Each statement was discussed and revised until a unanimous consensus was achieved. Results: A total of 16 recommendations for surgical amputation for patients with diabetic foot ulcers were formulated. Experts believe that Determination of the amputation plane should be comprehensively evaluated according to a patient's general health status, the degree of injury, the severity of lower limb vasculopathy. The Wagner grading system and the severity of diabetic lower extremity artery disease are important criterias when determining the degree of amputation. The severity of both diabetic foot infection and systemic underlying diseases are important factors when considering appropriate treatment. Moreover, consideration should also be given to a patient's socioeconomic status. Given the complexities of treating the diabetic foot, relevant issues in which consensus could not be reached will be discussed and revised in future. Conclusion: This expert consensus could be used to guide doctors in clinical practice, and help patients with diabetic foot ulcers gain access to appropriate amputation treatment.